Implementation of the I‐PASS handoff program in diverse clinical environments: A multicenter prospective effectiveness implementation study. Issue 1 (3rd November 2022) - Starmer, Amy J.; Spector, Nancy D.; O'Toole, Jennifer K.; Bismilla, Zia; Calaman, Sharon; Campos, Maria‐Lucia; Coffey, Maitreya; Destino, Lauren A.; Everhart, Jennifer L.; Goldstein, Jenna; Graham, Dionne A.; Hepps, Jennifer H.; et al.
Abstract: Background: Handoff miscommunications are a leading source of medical errors. Harmful medical errors decreased in pediatric academic hospitals following implementation of the I‐PASS handoff improvement program. However, implementation across specialties has not been assessed. Objective: To determine if I‐PASS implementation across diverse settings would be associated with improvements in patient safety and communication. Design: Prospective Type 2 Hybrid effectiveness implementation study. Settings and Participants: Residents from diverse specialties across 32 hospitals (12 community, 20 academic). Intervention: External teams provided longitudinal coaching over 18 months to facilitate implementation of an enhanced I‐PASS program and monthly metric reviews. Main Outcome and Measures: Systematic surveillance surveys assessed rates of resident‐reported adverse events. Validated direct observation tools measured verbal and written handoff quality. Results: 2735 resident physicians and 760 faculty champions from multiple specialties (16 internal medicine, 13 pediatric, 3 other) participated. 1942 error surveillance reports were collected. Major and minor handoff‐related reported adverse events decreased 47% following implementation, from 1.7 to 0.9 major events/person‐year ( p  < .05) and 17.5 to 9.3 minor events/person‐year ( p  < .001). Implementation was associated with increased inclusion of all five key handoff data elements in verbal (20% vs. 66%, p  < .001, n  = 4812) and written (10% vs. 74%, p  < .001, n  = 1787) handoffs, as well as increased frequency of handoffs with high quality verbal (39% vs. 81% p  < .001) and written (29% vs. 78%, p  < .001) patient summaries, verbal (29% vs. 78%, p  < .001) and written (24% vs. 73%, p  < .001) contingency plans, and verbal receiver syntheses (31% vs. 83%, p  < .001). Improvement was similar across provider types (adult vs. pediatric) and settings (community vs. academic).